Impact of local secondary gas addition on the dynamics of self-excited ethylene flames. (February 2021) - Hussain, Taaha; Talibi, Midhat; Balachandran, Ramanarayanan
Highlights: Efficacy of secondary gas addition on self-excited ethylene flames investigated. Gases added locally (2 mm upstream) to imperfectly-premixed flames. Effect of adding hydrogen, ethylene and nitrogen (control) compared. Hydrogen most effective in reducing magnitude of perturbations. Ethylene addition increased pressure and velocity oscillations. Abstract: Advanced combustion strategies for gas turbine applications, such as lean burn operation, have been shown to be effective in reducing NOx emissions and increasing fuel efficiency. However, lean burn systems are susceptible to thermo-acoustic instabilities which can lead to deterioration in engine performance. This paper will focus on one of the common industrial techniques for controlling combustion instabilities, secondary injection, which is the addition of small quantities of secondary gas to the combustor. This approach has often been employed in industry on a trial-and-error basis using the primary fuel gas for secondary injection. Recent advances in fuel-flexible gas turbines offers the possibility to use other gases for secondary injection to mitigate instabilities. This paper will explore the effectiveness of using hydrogen for this purpose. The experiments presented in this study were carried out on a laboratory scale bluff-body combustor consisting of a centrally located conical bluff body. Three different secondary gases, ethylene, hydrogen and nitrogen, were added locally to turbulent imperfectly-premixed ethylene flames. The total calories of the fuel mixture and the momentum ratio were kept constant to allow comparison of flame response. The heat release fluctuations were determined from the OH* chemiluminescence, while the velocity perturbations were estimated from pressure measurements using the two-microphone method. The results showed that hydrogen was the most effective in reducing the magnitude of self-excited oscillations. Nitrogen had negligible effect, while ethylene only showed an effect at high secondary flow rates which resulted in sooty flames.